PENINGKATAN SIMPANG TIGA TAK BERSINYAL PADA RUAS JALAN CIKEPUH KOTA SERANG - Ahmad Wildan Mauludi; Telly Rosdiyani; Ma'ulfi Kharis Abadi (Journal of Sustainable Civil Engineering (JOSCE), 2023)
Transportation has a very important role for people's lives. Judging from the current condition of Serang City, if viewed from the perspective of facilities and infrastructure, it has started to be inversely proportional. The Cikepuh intersection is an important intersection because motorists often pass it to get to the old Banten, East Serang Toll Road and the Rau main market. Where the need for roads is not proportional to the large number of existing vehicles. The increase in vehicle volume will affect the level of traffic performance which will eventually cause congestion. This study aims to determine performance factors and alternative strategies, methods of analysis using MKJI 1997. For data collection to calculate the volume of traffic flow by conducting a survey for 3 days, namely Monday, Saturday and Sunday, with an interval of 15 minutes and taken in the morning : 06.00-09.00, afternoon: 11.00-14.00, and afternoon: 16.00-18.00. Obtained the value of the degree of saturation (DS) of 2.4. Get a queue opportunity of QP% = 28.6% -75.9%, the average approach width of WI = 2.90m, the value of Degree of Saturation (DS) > 0.75. Exceeds established safety standards. The average capacity is 624.5 smp/hour, and it greatly affects the intersection delay (D) showing instability, namely 6.656 s/pcu. From the data attached to the Cikepuh intersection, there should have been an increase in the road, because it was not sufficient for motorists to pass through the intersection. Due to the lack of traffic lights and street lighting, the lack of road width and intersection geometry with increased driver capacity.